2012
DOI: 10.1051/0004-6361/201219057
|View full text |Cite
|
Sign up to set email alerts
|

The bimodal colors of Centaurs and small Kuiper belt objects

Abstract: Ever since the very first photometric studies of Centaurs and Kuiper belt objects (KBOs) their visible color distribution has been controversial. This controversy has triggered to a prolific debate on the origin of the surface colors of these distant icy objects of the solar system. Two scenarios have been proposed to interpret and explain the large variability of colors, hence surface composition. Are the colors mainly primordial and directly related to the formation region, or are they the result of surface … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 88 publications
7
98
1
4
Order By: Relevance
“…The Subaru hot KBO data nearly triple the number of high-S/N KBO color measurements between H=7 and H=9 contained in the Peixinho et al (2015) database and are instrumental in solidifying the observation of bimodality in that size range, which was previously hinted at using far fewer data points (Fraser & Brown 2012;Peixinho et al 2012Peixinho et al , 2015.…”
Section: Comparison With Larger Hot Kbosmentioning
confidence: 77%
See 2 more Smart Citations
“…The Subaru hot KBO data nearly triple the number of high-S/N KBO color measurements between H=7 and H=9 contained in the Peixinho et al (2015) database and are instrumental in solidifying the observation of bimodality in that size range, which was previously hinted at using far fewer data points (Fraser & Brown 2012;Peixinho et al 2012Peixinho et al , 2015.…”
Section: Comparison With Larger Hot Kbosmentioning
confidence: 77%
“…To date, hundreds of KBO colors have been measured, revealing the general properties of low albedos and reddish colors across the intermediate and small size ranges, extending down through objects with diameters of 50km and less (Hainaut et al 2012). Several studies have suggested a color bimodality among objects in the dynamically excited (i.e., hot) KBO population (e.g., Fraser & Brown 2012;Peixinho et al 2012;Lacerda et al 2014). A bimodal color distribution would have major implications for the formation of these bodies, indicating two types of surface compositions and perhaps two different formation environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not the first time that two spectrally distinct groups (i.e., a bimodality) are observed for relatively similar compositions among solar system small bodies. Emery et al (2011) reported the presence of two compositional groups among the Jupiter Trojans, while Tegler & Romanishin (1998) and later Peixinho et al (2012) reported the presence of two color groups among small TNOs and Centaurs.…”
Section: Compositional Analysis Of Our Meteorite and Asteroid Samplesmentioning
confidence: 99%
“…TNOs, in general, have red optical colors in g-, r-, and i-bands; even the "neutral" TNO surfaces, sometimes referred to as "blue" in the literature, are slightly redder than solar. It is well accepted that the small dynamically excited TNOs and Centaurs exhibit a bimodal color distribution, with red and neutral classes (e.g., Tegler & Romanishin 1998;Peixinho et al 2003Peixinho et al , 2012Peixinho et al , 2015Tegler et al 2003Tegler et al , 2016Wong & Brown 2017).…”
Section: Introductionmentioning
confidence: 99%